The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1046/j.1365-2982.2001.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal motor stimulation by the 5‐HT4 receptor agonist ML10302: differential involvement of tachykininergic pathways in the canine small bowel and colon

Abstract: 5-Hydroxytryptamine (5-HT)4 receptor agonists stimulate gut motility through cholinergic pathways, although there are data suggesting that noncholinergic (tachykininergic) excitatory pathways may also be involved. Differences may exist between the small bowel and colon. Our aims were: (i) to compare the prokinetic effect exerted by the 5-HT4 receptor agonist ML10302 in the canine small bowel and colon in vivo; and (ii) to investigate the role of tachykininergic pathways in mediating this response. In fasting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Further, close intra‐arterial injections of NK 1 receptor agonists stimulate giant migrating contractions of dog colon ( Tsukamoto et al , 1997 ) and antagonism at the receptor blocked increased defaecation induced by restraint stress in rats ( Ikeda et al , 1995 ) and blocked substance P‐ and stress‐induced defaecation by Monglolian gerbils, without affecting increases in defaecation evoked by 5‐HT or carbachol ( Okano et al , 2001 ). In conscious dogs, De Ponti et al (2001) found that NK 1 (or NK 2 or NK 3 ) receptor antagonism had no effects on propagated colonic myoelectrical events induced by 5‐HT 4 receptor activation, but reduced the associated increase in electrical spike or mechanical activity, an effect not observed with these antagonists in the small intestine. Together, these studies are consistent with an action of NK 1 receptors within the large bowel, although for the studies in vivo , a spinal site of action cannot always be ruled out.…”
Section: Nk1 Receptorsmentioning
confidence: 89%
“…Further, close intra‐arterial injections of NK 1 receptor agonists stimulate giant migrating contractions of dog colon ( Tsukamoto et al , 1997 ) and antagonism at the receptor blocked increased defaecation induced by restraint stress in rats ( Ikeda et al , 1995 ) and blocked substance P‐ and stress‐induced defaecation by Monglolian gerbils, without affecting increases in defaecation evoked by 5‐HT or carbachol ( Okano et al , 2001 ). In conscious dogs, De Ponti et al (2001) found that NK 1 (or NK 2 or NK 3 ) receptor antagonism had no effects on propagated colonic myoelectrical events induced by 5‐HT 4 receptor activation, but reduced the associated increase in electrical spike or mechanical activity, an effect not observed with these antagonists in the small intestine. Together, these studies are consistent with an action of NK 1 receptors within the large bowel, although for the studies in vivo , a spinal site of action cannot always be ruled out.…”
Section: Nk1 Receptorsmentioning
confidence: 89%
“…105 An in vivo study in dogs showed that tachykininergic pathways play an important role in mediating the colonic motor response to administration of the 5-HT 4 receptor agonist ML10302 whereas they are not involved in ML10302 induced prokinesia in the small bowel. 106 Besides these actions, 5-HT 4 receptors also affect secretory processes at the mucosal level. 107 There are animal 21 and human 108 data suggesting that 5-HT released by mucosal stimulation initiates a peristaltic reflex by activating 5-HT 4 receptors on sensory neurones containing calcitonin gene related peptide.…”
Section: -Ht 3 Receptor Agonists In Therapeutics: Preliminary Evidencementioning
confidence: 99%
“…Indeed, MEN10627 reduced restraint stress‐induced output of faecal pellets in rats (Evangelista, 2001). Finally, it should be noted that intestinal motor effects induced by the stimulation of other receptors (e.g., serotonin or protease‐activated receptors PAR‐2 and PAR‐4) are mediated in part by TKs acting through NK2 receptors ( De Ponti et al , 2001 ; Zhao & Shea‐Donohue, 2003; Mulè et al , 2004 ).…”
Section: Role Of Nk2 Receptors In the Control Of Intestinal Motility:mentioning
confidence: 99%